DIAGNOSTIC VALUE OF GALECTIN-3 LEVEL IN PATIENTS WITH CHRONIC HEART FAILURE AND TYPE 2 DIABETES - A. A. Snetkova; N. Yu. Timofeeva; V. S. Zadionchenko (Столичная издательская компания, 2015)
Currently, a greater emphasis is placed on the search for additional biomarkers of chronic heart failure (CHF). Galectin-3, a marker of fibrosis and inflammation, has shown himself as a biomarker of CHF in many studies, but the dynamics of its levels in patients with concomitant diabetes mellitus (DM) type 2 is not well-studied.Aim. To identify diagnostic significance of galectin-3 plasma level evaluation and its correlations with echocardiographic criteria for patients with CHF and DM type 2.Material and methods. The study included 33 patients with ischemic CHF (all patients had a history of myocardial infarction) and DM type 2. The patients were divided into two groups according to the left ventricle (LV) ejection fraction (EF): a group with CHF and preserved ejection fraction (PEF) (EF≥50%) and with CHF and reduced ejection fraction (EF<50%). Patients underwent clinical laboratory tests and Doppler echocardiography; moreover, the levels of brain natriuretic peptide (BNP) and galeсtin-3 were measured.Results. The mean level of galectin-3 in blood plasma in the group with CHF and PEF was significantly higher than in the group with CHF and reduced EF (p=0.007). In the group with CHF and PEF a positive correlation between the level of galectin-3 and diastolic LV function E/E' was found (r=0.620, p=0.01). A significant correlation between galectin-3 level and LV systolic function was stated in the group with reduced EF (r=0.53; p<0.05), while in the group with PEF, the correlation was not significant (p=0.225). In the group of patients with reduced EF a negative correlation between galectin-3 and the volume of left atrium was revealed (r=-0.53; p<0.05).Conclusion. Galectin-3 can be used as a diagnostic biomarker primarily in patients with CHF and PEF.